Theory of Change and agile community digital psychological interventions - Rad, Dana; Rad, Gavril (Technium Social Sciences Journal, 2021)
In today’s world, where new technologies are rapidly evolving, it is critical to understand the advancement of individual well-being when engaging with the digital world. Via the benefits of the internet’s vast scope, remote access, anonymity, and variety of formats, digital psychological therapies for mental wellbeing may help to improve access to mental health care. When technology is used to provide a therapeutic intervention, such as the internet, laptops, cell phones or tablets, and instant messaging systems, it is called digital intervention. For therapeutic approaches, evidence-based practice is critical, but there is disagreement on how to better promote real behavioral change. Digital Psychological Interventions framework for building and curating an information base for behavior improvement that can be used in the real world target the following services: (1) an intervention’s smallest, most meaningful, self-contained, and reproable behavior change modules; (2) computational designs that determine how modules, entities, and context interact; and (3) customization algorithms, which are judgment rules for strategy adjustment. Theory of Change (ToC) is gaining popularity in the wider debate on how to improve the execution of improvement programs and how to benefit from implementation especially in the mental health field. We describe the ToC as a management technique, an approach based on outcomes that extends critical thinking to the planning, execution, and assessment of policies and programs designed to support progress. Theory of Change (ToC) is a form of technique for strategy, engagement, and assessment that is used to facilitate social change in the organization, volunteerism, not-for-profit, and governmental agencies. Theory of Change identifies long-term priorities before mapping backward to determine required preconditions. A Theory of Change is a high-level, or macro, If-Then argument that states: If something is achieved, then these are the expected outcomes. The outcomes pathway is a series of required conditions applicable to a specific area of operation that are diagrammatically positioned in logical relationship to one another and associated with arrows that imply causality. All change initiatives are based on certain assumptions, but developing a theory of change will help make those assumptions clear to ensure that they are as well-founded as possible in previous study and experience.